Trend in rainfall associated with tropical cyclones in Mexico attributed to climate change and variability - Sinuhé Alejandro Sánchez Martínez; Fernando J. González Villarreal; Ramón Domínguez Mora; Maritza Liliana Arganis Juárez (Journal of Water and Climate Change, 2023)
The aim of this study was to investigate the existence and the magnitude of trend in different areas and durations of rainfall associated with tropical cyclones (TCR). To achieve this objective, a mixed-method approach was employed using depth–area–duration (DAD) and areal reduction factor (ARFs) curves that can be described as a logarithm equation to generate time series that allows the application of statistical methods such as the Mann–Kendall (MK) and Spearman Rho (SR) to detect trends. Time series are generated by substituting different areas in the logarithmic equations. The evidence presented shows that in Mexico, the TCR lasting 24 h shows an increasing trend for maximum areas between 300 and 1,700 km2 according to the MK and SR tests, respectively; according to these same tests for durations of 48 h, upward trends were observed up to maximum areas between 5,700 and 6,900 km2. The Sen's slope reports annual increases between 0.76 and 1.32 mm and between 1.15 and 2.06 for a duration of 24 and 48 h, respectively. In contrast, no trends were observed in the time series obtained from the ARFs. Finally, the Pettitt test reports an abrupt jump from the year 1997 in all cases. HIGHLIGHTS This study establishes a quantitative framework to detect trends in rainfall associated with tropical cyclone (TC) through time series originating from calculating depth–area–duration and areal reduction factor curves.; This methodology allows the search for trends for rainfall associated with different areas and durations.; The maximum area for a certain duration in which there is a trend can be determined.; The methodology is applicable regionally in any area where TCs are present.;